BUILDING THE APOTHEOSIS: THE CONSOLIDATION OF THE PRESIDENTIAL INAUGURATION CEREMONY IN COSTA RICA (1940-1949) - Díaz González, José Andrés (2015)
During the 1940`s, the ceremony of inauguration of the President had been consolidated as a political ritual that allows the new government to gain legitimacy and visibility, through the staging of the power. In additional, this ceremonies taken a character of civic celebration that facilitates the process of a national`s reconciliation after the struggle for control of the political power.